Sleep bruxism and temporomandibular disorder: Clinical and polysomnographic evaluation - Camparis, Cinara Maria [UNESP]; Formigoni, Gilberto; Teixeira, Manoel Jacobsen; Bittencourt, Lia Rita Azeredo; Tufik, Sérgio; Siqueira, José Tadeu Tesseroli de (Elsevier, 2006)
Objective: To seek better understanding of chronic musculoskeletal facial pain and its relation to sleep bruxism, by comparing patients with sleep bruxism, with and without temporomandibular disorder. Design: Forty sleep bruxism patients were evaluated according to the Research Diagnostic Criteria for Temporomandibular Disorders: group A-20 patients with myofascial pain, 3 men, 17 women; average age 32.7 yr; mean duration of pain 4.37 yr; group B-20 without myofascial pain, 5 men, 15 women; average age 30.8 yr. Sleep and bruxism were evaluated in one-night polysomnography. Results: There were no statistically significant differences for bruxism and sleep variables of the two groups: number of bursts and bruxism episodes per hour, amplitude and duration of bruxism episodes, sleep efficiency and latency, percentage of non-REM and REM sleep, respiratory events, periodic limb movements, and micro-arousals. Conclusions: The polysomnographic characteristics of patients with sleep bruxism, with and without orofacial pain, are similar. More studies are necessary to clarify the reasons why some sleep bruxism patients develop chronic myofascial pain, and others do not. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Bruxism; Facial pain; Myofascial pain; Sleep; Temporomandibular disorders; adolescent; adult; bruxism; chronic disease; comparative study; electromyography; face pain; female; headache; human; male; middle aged; pain assessment; pathophysiology; polysomnography; sleep stage; temporomandibular joint; temporomandibular joint disorder; Adolescent; Adult; Chronic Disease; Electromyography; Facial Pain; Female; Headache; Humans; Male; Middle Aged; Pain Measurement; Polysomnography; Sleep Bruxism; Sleep Stages; Temporomandibular Joint; Temporomandibular Joint Disorders